Zad .1.
a) a+(a+b)
b) 2x-(x+4)
c) 7-(-x+6)
d) -(x+4)+(x-5)
e) 1-(t+p)-(t-2)
f) -(-y+2)+(-2y-4)
Zad.2.
a) 6(x-4)-2
b) 2(x+1)-3(x-1)
c) -3(y-2)+4(y+2)
d) 5(x-y-1)-4(x+2)
e) 2(3a+b)-2(a-b)
f) ½(4x-4)-2x
g) x(x-1)-3(x²-x)
h) 5a(a-3)-3a(a-5)
i) 3x(x+⅓y)-2y(½x-½)

2

Odpowiedzi

2010-03-01T19:12:15+01:00
1.a)2a+b
b)x-4
c)1+x
d)-9
e)3-2t-p
f)y-6
2.a)6x-22
b)6+y
c)y+12
d)x-5y-9
e)4a+4b
f)-2
g)4x-3x kwadrat
h)2a kwadrat
i)??
1 3 1
2010-03-01T19:20:19+01:00
A) a+(a+b)=a+a+b=2a+b
b) 2x-(x+4)=2x-x-4=x-4
c) 7-(-x+6)=7+x-6=1+x
d) -(x+4)+(x-5)=-x-4+x-5=-11
e) 1-(t+p)-(t-2)=1-t-p-t+2=3-2t-p
f) -(-y+2)+(-2y-4)=y-2-2y-4=-y-6
Zad.2.
a) 6(x-4)-2=6x-24-2=6x-26
b) 2(x+1)-3(x-1)=2x+2-3x+3=-x+5
c) -3(y-2)+4(y+2)=-3y+6+4y+8=y+14
d) 5(x-y-1)-4(x+2)=5x-5y-5-4x-2=x-5y-7
e) 2(3a+b)-2(a-b)=6a+2b-2a+2b=4a+4b
f) ½(4x-4)-2x=2x-2-2x=-2
g) x(x-1)-3(x²-x)=x²-x-3x²+3x=-2x²+2x
h) 5a(a-3)-3a(a-5)=5a²-15a-3a²+15a=2a²
i) 3x(x+⅓y)-2y(½x-½) 3x²+xy-xy+1=3x²+1
1 5 1